Towards a Unity of Dos Passos's and Hemingway's Aesthetics in The Spanish Earth - Tydal, Fredrik (The Grove - Working Papers on English Studies, 2016)
In this article, I argue that The Spanish Earth, as the first and only artistic collaboration between John Dos Passos and Ernest Hemingway, represents a unique fusion of their different aesthetics. In doing so, I hope to show that all the drama surrounding the production of the film has come to obscure the essential unity of the work itself. For despite the fraught circumstances, I believe that Dos Passos and Hemingway were able to put their aesthetic differences aside for their mutual love of Spain, even as the production itself would paradoxically lead to their falling out.